Implementing the National Education Policy 2020 in Himachal Pradesh: Difficulties and Opportunities from the Perspective of Stakeholder (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The goal of this research study is to examine the challenges that are associated with the the implementation of the NEP 2020 in Himachal Pradesh, India, and to propose a solution to address these challenges. The NEP 2020 presents a comprehensive reform agenda that is designed to revolutionise the Indian education system. It advocates for experiential learning, the incorporation of technology, and skill development, as well as holistic and interdisciplinary education. Although the policy has ambitious objectives, it must overcome obstacles such as inadequate capacity, resources, and organisational preparedness in order to ensure its successful implementation. The paper proposes a variety of solutions to address these challenges, such as the active involvement of stakeholders, robust monitoring and evaluation mechanisms, resource mobilisation efforts, and enhanced coordination with the central government. The effective implementation of NEP 2020 in Himachal Pradesh is contingent upon the implementation of these strategies. In summary, the paper emphasises the potential of NEP 2020 for the system in Himachal Pradesh, but only if the policy is implemented effectively and the identified challenges are adequately addressed.